Grammatische Merkmale der deutschen und arabischen Rechtssprache – eine kontrastive Studie am Beispiel der verwaltungsgerichtlichen Urteile in Deutschland und Ägypten [Grammatical characteristics of German and Arabic legal language – a contrastive study on the example of administrative court judgments in Germany and Egypt] - Shemy, Amany (Comparative Legilinguistics, 2024)
This contrastive study deals with the legal grammar of German and Arabic administrative court judgments. On the basis of a selection of recent judgments of several administrative courts in Germany and Egypt, sentence types, use of the verb as well as condensation forms such as nominalization and attribute series are examined. The study reveals a number of notable parallel trends in both legal systems. Long hypotactic sentence constructions dominate, which are usually difficult to understand. However, the complexity of the sentence structure is not the same in all parts of the administrative court judgments of the two languages. The two legal languages also have in common the tendency towards a compact style. Many complex nominal forms are often embedded in sentence constructions, which serve to replace subordinate clauses. However, the two legal languages differ with regard to the use of connectors, active/passive forms and modality expressions as well as tense forms.